2015
DOI: 10.1007/s00217-015-2572-1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of phenolic acids isolated from green and roasted boiled-type coffee brews to total coffee antioxidant capacity

Abstract: 50 % (on average over 36 and 45 % in green and roasted coffee extracts, respectively). Significant differences between the AC values determined for CB and PA samples were noticed only for the MCA and DPPH methods which reflect the different molecular mechanisms underlying each of the assays. Additionally, the statistical methods, including principal component analysis, applied to results of antioxidant capacity obtained with different analytical techniques confirmed their feasibility to distinguish between cof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 62 publications
7
61
0
Order By: Relevance
“…However, it was observed that roasted non-defective coffee beans exhibited significantly higher antioxidant activities compared to roasted defective coffee beans. The results in this study agrees with the study of Górnaś et al (2016), indicating a lower contribution of phenolic compounds to metal chelating activities of roasted coffee bean extracts.…”
Section: Figsupporting
confidence: 92%
See 3 more Smart Citations
“…However, it was observed that roasted non-defective coffee beans exhibited significantly higher antioxidant activities compared to roasted defective coffee beans. The results in this study agrees with the study of Górnaś et al (2016), indicating a lower contribution of phenolic compounds to metal chelating activities of roasted coffee bean extracts.…”
Section: Figsupporting
confidence: 92%
“…It has to be noted that other notable compounds which have been extensively published elsewhere regarding other contents of coffee extracts such as phenolic compounds (Ramalakshmi et al, 2009;Górnaś et al, 2016), biogenic amines such as putrescine, cadaverine, spermidine, spermine and tryptamine (Vasconselos et al, 2007), proteins, carbohydrates, fatty acids (Oliveira et al, 2006), several volatile compounds (Toci and Farah, 2008) and diterpenes such as cafestol and kahweol (Cavin et al, 1998). However, unwanted contaminants such as mycotoxins may also be present (Taniwaki et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples of 1 st class Arabica coff ee roasted at 171°C had signifi cantly higher (P < 0.05) antioxidant activity (DPPH) than coff ee samples roasted at 167°C and 175°C. Górnaś et al (2016) found that antioxidant activity (DPPH) decreases during the roasting process and is higher in medium-roasted coff ee samples than in dark-roasted coff ee samples. Antioxidant activity based on the results of the ABTS test was highest in 1 st class Arabica coff ee roasted at 167°C, and lowest in coff ee roasted at 175°C (Table 5).…”
Section: Resultsmentioning
confidence: 96%